New requirements and new forms of protection in the Italian administrative process - Montedoro, Giancarlo (2011)
This article first considers the need for protection in administrative law and various actions for annulment in Italy. Next, it takes a closer look at the different forms of protection available in civil law and common law in the country. Finally, the principle of effectiveness and the new jurisdiction of administrative judges are examined in the Italian context. -Reproduced.
Keywords: Public administration - Italy; Public administration